2022
DOI: 10.3390/v14061188
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Involvement in SARS-CoV-2 Infection

Abstract: SARS-CoV-2 has evolved into a virus that primarily results in mild or asymptomatic disease, making its transmission more challenging to control. In addition to the respiratory tract, SARS-CoV-2 also infects the digestive tract. Some gastrointestinal symptoms occur with or before respiratory symptoms in patients with COVID-19. Respiratory infections are known to cause intestinal immune impairment and gastrointestinal symptoms. When the intestine is inflamed, cytokines affect the lung immune response and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 141 publications
0
24
0
2
Order By: Relevance
“…Angiotensin-converting enzyme 2 receptors and transmembrane serine protease are highly expressed in gastrointestinal epithelial cells and provide a favorable route for viral entrance [ 10 ]. Gastrointestinal involvement is attributed to direct viral attack and inflammatory response secondary to the activation of inflammatory cytokines with subsequent activation of anti-inflammatory or protective cytokines [ 3 ]. SARS-CoV-2 viral RNA has been encountered in the stool samples from infected patients [ 11 ] in addition to the detection of SARS-CoV-2 RNA in tissue histology from infected individuals [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin-converting enzyme 2 receptors and transmembrane serine protease are highly expressed in gastrointestinal epithelial cells and provide a favorable route for viral entrance [ 10 ]. Gastrointestinal involvement is attributed to direct viral attack and inflammatory response secondary to the activation of inflammatory cytokines with subsequent activation of anti-inflammatory or protective cytokines [ 3 ]. SARS-CoV-2 viral RNA has been encountered in the stool samples from infected patients [ 11 ] in addition to the detection of SARS-CoV-2 RNA in tissue histology from infected individuals [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…GIT involvement is attributed to viral direct invasion into intestinal tract cells in addition to immune host reaction [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, different authors have reported in literature the possibility, more than suggestive, of a connection between COVID-19 infection and intestinal microbiota dysbiosis, considering that, in COVID-19 patients with severe intestinal dysfunction, the presence of virions in fecal, oral, and gastrointestinal samples was found in a range between 2% and 36% [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The most commonly reported intestinal symptoms related to COVID-19 could be mild as nausea and stomach discomfort or more intense such as vomiting and diarrhea [ 27 , 52 , 53 , 54 , 55 ].…”
Section: Microbiota and Sars-cov-2 Infectionmentioning
confidence: 99%
“…Os indivíduos podem sofrer danos mais graves e menos comuns, como, por exemplo, isquemia mesentérica, pelo desenvolvimento de trombos no sistema circulatório próximo à região, ou sintomas mais leves e mais frequentes, como náuseas, vômitos, dor e distensão abdominal. Outro sintoma comumente relatado é a diarreia, decorrente do processo inflamatório e da agressão celular sofrida pelos enterócitos (Chen, et al, 2022).…”
Section: • Efeitos Sistêmicos Do Coronavírusunclassified